Case of summer-type hypersensitivity pneumonitis complicated with IgA nephropathy. Issue 6 (18th June 2019) - Maetani, Tomoki; Shima, Hiroshi; Shiraishi, Yusuke; Marumo, Satoshi
Abstract : Association between pulmonary disease and IgA nephropathy (IgAN) has been previously reported. However, no association has been reported between hypersensitivity pneumonitis (HP) and IgAN. Here, we report about a patient with no particular medical history, who experienced worsening dyspnoea in the course of 1 month, with ground-glass opacity on chest CT and no improvement after antibiotic therapy. The patient was diagnosed as having HP based on the history of antigen exposure, detection of Trichosporon asahii -specific antibodies and bronchoscopy findings. Concomitantly, findings of renal biopsy revealed the IgAN diagnosis. The patient underwent corticosteroid therapy, with good outcomes for both HP and IgAN. This is the first report in the literature to describe summer-type HP complicated with IgAN.